A peptide-CpG-DNA-liposome complex vaccine targeting TM4SF5 suppresses growth of pancreatic cancer in a mouse allograft model - Park, Sangkyu (Onco Targets Ther, 2018)
BACKGROUND: Patients with pancreatic cancer have a poor prognosis and are usually diagnosed at a late stage. Because TM4SF5 is known to be overexpressed in hepatocellular carcinoma, colon cancer, and pancreatic cancer, it is considered as one of the candidate molecular targets for an anticancer strategies. PURPOSE: The purpose of this study was to evaluate possible utility of TM4SF5 to treat pancreatic cancer using a mouse allograft model. MATERIALS AND METHODS: We analyzed expression of TM4SF5 in pancreatic cancer tissues using immunohistochemistry. We established a mouse pancreatic cancer cell line stably expressing TM4SF5 and identified the effect of TM4SF5 expression in vitro. We used the CpG-DNA-peptide-liposome complex as a peptide vaccine and investigated antitumor effects of the vaccine in a mouse model with TM4SF5 expressing pancreatic cells. To investigate the function of produced antibody, we evaluated effects of the anti-TM4SF5 monoclonal antibody in vitro in terms of cell growth and migration properties. RESULTS: Immunohistochemical analysis showed that 36.4% of pancreatic cancer tissue samples expressed TM4SF5. Expression of TM4SF5 induced increased cell proliferation and motility in vitro. Injection of the TM4SF5 peptide vaccine induced the production of anti-hTM4SF5 antibodies and reduced the growth of pancreatic tumors in mice established by subcutaneous injection of the TM4SF5-expressing mouse pancreatic cancer cell line. The treatment of TM4SF5-expressing cells with the anti-hTM4SF5 monoclonal antibody reduced cell growth, modulated the expression of the epithelial–mesenchymal transition markers Vimentin and E-cadherin, and decreased cell motility in vitro. CONCLUSION: Our results showed that the TM4SF5 peptide vaccine had a protective effect against pancreatic tumors expressing TM4SF5, and this effect was mediated, at least in part, by the production and suppressive function of the anti-TM4SF5 antibodies. Therefore, we suggest that targeting TM4SF5 could be a novel strategy to prevent or treat pancreatic cancer.